IMPLEMENTASI MODEL PjBL BERBANTUAN MOBILE LEARNING TERHADAP KETERAMPILAN BERPIKIR KRITIS PEMBELAJARAN IPAS SISWA KELAS 5 SDN PENDRIKAN LOR KOTA SEMARANG - Utomo, Eko Prasetyo; Sutopo, Yeri; Yulianto, Arief; Sumartiningsih, Sri; Yuwono, Agus (Universitas Wahid Hasyim Semarang, 2024)
Kurikulum Merdeka is a replacement for the 2013 curriculum, this curriculum contains planning in learning activities and a process of gaining knowledge, as well as experience that we get from learning activities. This curriculum change requires teachers to readjust the learning model that appropriate with Kurikulum Merdeka, where teachers are facilitators and students are active in the learning process. This study aims to analyze the implementation of Kurikulum Merdeka and the application of Project Based Learning (PJBL) help by mobile learning in IPAS Learning in Elementary School. The method used in this study is descriptive qualitative with a case study approach. Data collection techniques used interviews and observations. The subjects in this study were the Principal and Class V Teachers of SDN Pendrikan Lor. Data analysis starts with data reduction, data presentation, and conclusion. The results of this study indicate that the Kurikulum Merdeka and Project Based Learning (PjBL) with mobile learning has been implemented in Class V. The implementation of Project Based Learning in mathematics learning is carried out in several stages, namely preparation stage and implementation stage. This learning model involves many student roles to create an interesting and attractive learning process